The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1071/sb00039
|View full text |Cite
|
Sign up to set email alerts
|

Higher-level relationships among the eucalypts are resolved by ITS-sequence data

Abstract: This expanded survey of ITS sequences represents the largest analysis of molecular data ever attempted on Eucalyptus. Sequences of the internal transcribed spacer (ITS) region of the nuclear ribosomal DNA were included in an analysis of 90 species of Eucalyptus s.s. and 28 species representing eight other genera (Allosyncarpia, Angophora, Arillastrum, Corymbia, Eucalyptopsis, Stockwellia, Lophostemon and Metrosideros). The results of the study indicate that Angophora and Corymbia form a well-supported clade th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(137 citation statements)
references
References 17 publications
8
128
1
Order By: Relevance
“…Although only a few taxa from the present study were included in more recent phylogenies, the relationships found here were generally consistent with the findings of Steane et al (1999Steane et al ( , 2002Steane et al ( , 2011, for the relationship of Eucalyptus obliqua and E. regnans) and Bayly and Ladiges (2007, for the close relationship of E. triflora, E. spectatrix and E. paliformis). The results from the present study support many of the relationships proposed by Ladiges et al (1989), Hill (2002) and Brooker (2000).…”
Section: Phylogenetic Relationships and The Monophyly Of The Green Ashessupporting
confidence: 86%
See 2 more Smart Citations
“…Although only a few taxa from the present study were included in more recent phylogenies, the relationships found here were generally consistent with the findings of Steane et al (1999Steane et al ( , 2002Steane et al ( , 2011, for the relationship of Eucalyptus obliqua and E. regnans) and Bayly and Ladiges (2007, for the close relationship of E. triflora, E. spectatrix and E. paliformis). The results from the present study support many of the relationships proposed by Ladiges et al (1989), Hill (2002) and Brooker (2000).…”
Section: Phylogenetic Relationships and The Monophyly Of The Green Ashessupporting
confidence: 86%
“…The phylogenies produced here were more resolved than were previous phylogenies of subgenus Eucalyptus using traditional one-region sequence data (e.g. Steane et al 1999Steane et al , 2002Bayly and Ladiges 2007). These findings demonstrate that phylogenetic analyses based on DArT markers can provide insights into evolutionary relationships among Table 2 (Column 6).…”
Section: Phylogenetic Relationships and The Monophyly Of The Green Ashesmentioning
confidence: 87%
See 1 more Smart Citation
“…Although based on a small sample of eudesmid species, analyses of Sale et al (1993, chloroplast DNA) and Udovicic and Ladiges (2000, chloroplast and nuclear DNA) provided further support for the monophyly of the subgenus, in addition to morphology discussed above. In a large sample of ITS nuclear rDNA sequences for species of Eucalyptus, including six eudesmids, Steane et al (2002) also found subgenus Eudesmia to be monophyletic, and related to subgenus Eucalyptus (the 'monocalypt' clade) and E. tenuipes (Maiden & Blakely) Blakely & C.T.White, although nodes lacked bootstrap support.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Outgroup taxa included were E. curtisii Blakely & C.T.White (monotypic subgenus Acerosae), E. tenuipes (subgenus Cuboidea) and E. cloeziana F.Muell. (monotypic subgenus Idiogenes) based on previous eucalypt studies Sale et al 1996;Steane et al 2002). As indicated by their treatment as subgenera by Brooker (2000), there is evidence from morphology and molecular data that these species are outside the main clades of Eucalyptus (subgenera Eudesmia, Eucalyptus and Symphyomyrtus) and therefore they are useful as outgroups.…”
Section: Samplingmentioning
confidence: 99%